"Ugly" Architectural Drawings of William Hardy Wilson: (Re)Viewing Architectural Drawings with Difficult Origins or Content for Curation and Display. Issue 3 (3rd July 2021) - Putra, Yvette
Abstract: This article identifies architectural drawings as "ugly" not aesthetically, but where there are difficult origins or content. It argues for an explicit methodology for their curation and display. The twentieth- and twenty-first-century shift in the viewing of architectural drawings has brought architectural drawings closer to artworks for public consumption. However, the recent reassessment of cultural artifacts clashes with the widely accepted cultural and social mores. By examining drawings by the Australian architect William Hardy Wilson (1881–1955), this article proposes recommendations for the curation and display of ugly architectural drawings that are borrowed from other fields that have made progress in managing similar problems. By testing the recommendations against Hardy Wilson's drawings, this article shows that contextualizing and acknowledging the offensive nature of his drawings allows for a critical reckoning of Australian architecture across the scholarly, industrial and public spheres.